Evaluasi Safety Maturity Level Dengan Metode Saaty Di Tambang PT Mitra Stania Prima, Desa Cit/Mapur Kabupaten Bangka.: Evaluation of the Safety Maturity Level Using the Saaty Method at PT Mitra Stania Prima Mining Site, Cit/Mapur Village, Bangka Regency - Lingga, Yesi Crystiyanti Hangelina Br; Franto; Harsiga, Edwin (MINERAL, 2025)
This study aims to evaluate the Safety Maturity Level within the mining industry using the Analytical Hierarchy Process (AHP) method developed by Saaty, allowing for objective and systematic prioritization of influencing factors. A case study was conducted at PT. Mitra Stania Prima, a tin mining company, with the assessment framework referring to the Decree of the Director General of Mineral and Coal No. 10.K/MB.01/DJB.T/2023 concerning the measurement of mining safety maturity levels. The evaluation considered four key indicators: Worker Participation (weight: 0.134, categorized as Proactive), Responsibility of Work Unit Leadership (weight: 0.296, Proactive), Accident and Occupational Disease Statistics and Analysis (weight: 0.164, Planned), and Control Efforts (weight: 0.216, Planned). The results indicate that PT. Mitra Stania Prima achieved a total score of 0.806, placing it at Level 4 (Proactive) on the Safety Maturity Level scale. The most influential factor was the Responsibility of Work Unit Leadership (eigenvalue: 0.44), followed by Control Efforts (eigenvalue: 0.39). It can thus be concluded that the company's current safety maturity is categorized as Proactive, with a final score of 0.81. To achieve the highest level, Resilient (score of 1.00), the company is advised to improve by 0.09 points by strengthening critical aspects, including addressing safety audit findings, digitalizing safety documentation, and involving third-party vendors in enhancing overall safety maturity.